Hyponormality of Toeplitz Operators on Symmetric-type Circulant Trigonometric Polynomial Symbols: An Extremal Case - Phukon, Ambeswar; Narzary, Nabani (Communications in Mathematics and Applications, 2024)
In this paper, we give some necessary and sufficient conditions to determine the hyponormality of Toeplitz operators on symmetric-type circulant trigonometric polynomial symbols in Hardy-Hilbert spaces of analytic functions considering an extremal case.